Transformational Leadership: Hard Working, Smart Working, Qualified Working, Sincere Working and Completed Work - Karsono, Bambang (Dinasti International Journal of Economics, Finance & Accounting, 2023)
Transformational Leadership: Hard Working, Smart Working, Qualified Working, Sincere Working and Completed Work is a literature review article within the scope of leadership science. The purpose of this article is to build a role hypothesis between variables that will be used in further research on the concept of leadership. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. The Article writing method is library research, from e-books and open access e-journals. The results: 1) Hard working plays a role in transformational leadership; 2) Smart working plays a role in transformational leadership; 3) Qualified working plays a role in transformational leadership; 4) Sincere working plays a role in transformational leadership; 5) Completed work plays a role in transformational leadership. Other factors that affect Transformational Leadership including: work culture, motivation and work environment.